2020
DOI: 10.2147/ijn.s255486
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Magnesium-Incorporated Nanoporous Titanium Coating for Rapid Osseointegration</p>

Abstract: Purpose Micro-arc oxidation (MAO) is a fast and effective method to prepare nanoporous coatings with high biological activity and bonding strength. Simple micro/nano-coatings cannot fully meet the requirements of osteogenesis. To further improve the biological activity of a titanium surface, we successfully added biological magnesium (Mg 2+ ) to a coating by micro-arc oxidation and evaluated the optimal magnesium concentration in the electrolyte, biocompatibility, cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Gao et al 35 have demonstrated an increase in ALP activity and osteogenic gene expression in MC3T3-E1 cells exposed to Mg-coated Ti6Al4V. Li et al 36 evaluated the osteogenic properties of a nanoporous titanium coating with different concentrations of magnesium acetate, which was able to promote the adhesion, proliferation, and differentiation of bone marrow mesenchymal stem cells (BMSCs).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al 35 have demonstrated an increase in ALP activity and osteogenic gene expression in MC3T3-E1 cells exposed to Mg-coated Ti6Al4V. Li et al 36 evaluated the osteogenic properties of a nanoporous titanium coating with different concentrations of magnesium acetate, which was able to promote the adhesion, proliferation, and differentiation of bone marrow mesenchymal stem cells (BMSCs).…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic coating and 3D-printed microporous implant can further improve the local antibiotic concentration. For instance, Li X et al (2020) developed a 3D-printed intervertebral cage covered with polyvinyl alcohol coating loaded with vancomycin that could effectively inhibit the reproduction of Escherichia coli , S. epidermidis, and S. aureus ( Figure 6 ). Moreover, the combination of antibiotics and Ag + may produce synergistic effects, reducing bacterial drug resistance and playing a stronger antibacterial function.…”
Section: Functionalization Of the Implant Surfacementioning
confidence: 99%
“…Strategies for the modification of titanium are mediated by adding specific elements, such as bioactive molecules (including PRF 75 and BMP 76 ) and inorganic metallic ions (e.g., magnesium 77 ). Via modification, the surface morphology of titanium has shown goal-directed reformation, which is more suitable for surrounding cells (such as BMSCs) to adhere and facilitate osteogenic differentiation (enhanced alkaline phosphatase (ALP) expression and calcium deposits).…”
Section: Biomaterials For Maxillofacial Bone Defect Repairmentioning
confidence: 99%